2018
DOI: 10.13053/cys-22-2-2950
|View full text |Cite
|
Sign up to set email alerts
|

A Generalization of the Averaged Hausdorff Distance

Abstract: The averaged Hausdorff distance ∆p is an inframetric which has been recently used in evolutionary multiobjective optimization (EMO). In this paper we introduce a new two-parameter performance indicator ∆p,q which generalizes ∆p as well as the standard Hausdorff distance. For p, q 1 the indicator ∆p,q (that we call the (p, q)-averaged distance) turns out to be a proper metric and preserves some of the ∆p advantages. We proof several properties of ∆p,q, and provide a comparison with ∆p and the standard Hausdorff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…In particular, this is a natural setting in multi-objective optimization because the solution of such a problem typically forms a set of certain dimension (and is thus not given by finitely many points). We have shown that the extended indicators keep the nice metric properties from its finite-version predecessors (see [14,26]). Moreover, for GD p,q , sufficient conditions have been provided ensuring that certain compliance to Pareto optimality of this indicator can be guaranteed.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In particular, this is a natural setting in multi-objective optimization because the solution of such a problem typically forms a set of certain dimension (and is thus not given by finitely many points). We have shown that the extended indicators keep the nice metric properties from its finite-version predecessors (see [14,26]). Moreover, for GD p,q , sufficient conditions have been provided ensuring that certain compliance to Pareto optimality of this indicator can be guaranteed.…”
Section: Discussionmentioning
confidence: 92%
“…With the aid of Theorem 1 we generalize the results of [26] (Section 3). For easy reference, we provide here slightly abbreviated but complete proofs.…”
Section: Definition Of ∆ Pq For Measurable Setsmentioning
confidence: 85%
See 3 more Smart Citations